Effect of Different Cryopreservation Regimens on Integrity of Bone Marrow Stem Hemopoietic Cells in Animals with Autoimmune Diseases. Part 1. In vitroEstimation of Functional Status of Cryopreserved Bone Marrow Hemopoietic Precursors - Goltsev, A. N.; Dubrava, T. G.; Kozlova, Yu. A.; Ostankov, M. V.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2005)
Functional characteristics of hemopoietic stem cells (HSCs) of bone marrow (BM) in healthy animals and those with autoimmune diseases (AIDs) before and after cryopreservation using different regimens were in vitro determined. Fundamental differences of a change in functional status of hemopoietic precursors in healthy and AIDs donors under the same changes in cryopreservation conditions are shown. It was noted, that varying concentrations of cryoprotectant at the same freezing rate enabled to point out the optimum of conditions, under which the cryopreservation factors equally affected both functional status of hemopoietic cells of different differentiation rate and BM, procured from different donors (physiology and pathology). At he same time different freezing rates have identical parameters of a selective effect on SHCs with a certain differentiation level in healthy and â€œpathologicalâ€ BM. Different cryopreservation conditions were established to be the optimal ones in respect to providing functional potential of these cells in both BMs. Thus, the maximum number and the most balanced subpopulation composition of hemopoietic precursors as colony-forming units of granulomonocytopoiesis (CFU-GM) and forming colonies in spleen of lethally irradiated recipients (CFUs) of healthy animalsâ€™ BM were preserved after freezing with 1Â°C/min rate and 10% dimethyl sulfoxide (DMSO) and 40Â°C/min with 10% DMSO for BM of AIDs animals. The relevance of idea, recently given by authors about the possibility to use cryopreservation as a factor of directed regulation of bioobjectâ€™s state and, in particular, BM hemopoietic precursors with different initial status is emphasized with a specific example.